VIDEO ANIMASI DAN PPT DAPAT MENINGKATKAN PENGETAHUAN TENTANG KONSUMSI SAYUR DAN BUAH PADA SISWA SEKOLAH DASAR - Priawantiputri, Witri; Mahmudah, Umi; Rahmat, Mamat; Rahmawati, Risa (Media Penelitian dan Pengembangan Kesehatan, 2023)
Good nutritional intake is very important to support the growth and development of school-aged children. However, consumption of vegetables and fruit among school-aged children is very low. Therefore, educational media is needed to influence knowledge, attitudes and behavior in consuming vegetables and fruit. This research aimed to determine the effect of nutrition education using video on knowledge, attitudes and consumption of vegetables and fruit. This research was an experimental research with a quasi experimental design with pre test - post test with a sample of 62 grade 4 students at Pasirkaliki 156 Elementary School Bandung. Analysis of mean differences before and after intervention used Wilcoxon Test (data is not normally distributed). Mann Whitney test was used to see the difference between control and treatment groups (P<0.05 and CI 95%). There was a significant difference in students' knowledge scores between before and after being given nutrition education in the two groups. In this study, there was an increase in the average knowledge score of 2.94 points in the treatment group and 2.35 points in the control group. Attitude score average was increase 3.29 points in treatment group and 3.29 points in control group. However, changes in the average consumption of vegetables and fruit in the treatment group were lower than the control group. The research showed that animated video and power point media can be used to increase elementary school students' knowledge regarding vegetable and fruit consumption.